Effects of photobiomodulation on wound contraction in rats undergoing doxorubicin extravasation: a histomorphometric analysis - Karina Alexandra Batista da Silva Freitas; Noeme Sousa Rocha; Eliana Maria Minicucci; Valéria Flávia Batista da Silva; Hélio Langoni; Regina Célia Popim (SciELO, 2021)
ABSTRACT Objective: To analyze wound contraction and histomorphometric pattern of lesions in Wistar rats undergoing doxorubicin extravasation. Method: Sixty adult female rats were used, divided into four groups of fifteen animals: Group 1 (Control, without antidote); Group 2 (Hyaluronidase); Group 3 (Photobiomodulation), and Group 4 (Hyaluronidase + Photobiomodulation). Doxorubicin 1mg (0.5 ml) was applied subcutaneously on the animals' back, inducing the wound. Macroscopic and morphometric evaluation of the lesions was performed every two days for 28 days. On the 30th day, euthanasia was performed and the material was collected for histological evaluation. Results: The animals in the photobiomodulation and photobiomodulation + Hyaluronidase groups presented regeneration tissue with neovascularization and acute inflammation, with improvement in wound healing, which did not occur in the other groups. The contraction rates were better in those treated with photobiomodulation and photobiomodulation + Hyaluronidase, with healing percentages of 76.6% and 72.1%, respectively. Conclusion: The combination of photobiomodulation (660 nm-1 J) with topical hyaluronidase (65 UTR) proved to be effective in the process of wound healing due to extravasation of doxorubicin, and can be incorporated into the practice of clinical oncology.